The locked room - Griffiths, Elly (Griffiths, Elly. Ruth Galloway mystery, 2022)
Nelson, investigating a series of murder-suicides he has connected to an archaeological discovery--and to Ruth's seemingly sweet new neighbor, Zoe--he enlists Ruth's help until she, Zoe, and Kate go missing and he is left scrambling to find them before it's too late.